Altered Visual and Proprioceptive Spatial Perception in Individuals with Parkinson's Disease. Issue 1 (February 2020) - José Luvizutto, Gustavo; Souza Silva Brito, Thanielle; de Moura Neto, Eduardo; Aparecida Pascucci Sande de Souza, Luciane
Difficulties in the integration of visual, vestibular, and somatosensory information in individuals with Parkinson's disease (PD) may alter perception of verticality. Accordingly, in this cross-sectional study, we analyzed PD patients' ( n = 13) subjective visual vertical (SVV) and subjective haptic vertical (SHV) perceptions and compared them to those of healthy controls ( n = 14). We compared SVV and SHV findings among participants with PD, healthy controls, and cutoff points of normality based on prior research literature, using the parametric nonpaired t test (at p < .05) and Cohen's d (at d > 0.8) to determine clinical relevance. We analyzed SVV with the bucket test and SHV with the rod rotations task in clockwise and counterclockwise directions. We calculated Pearson correlations to analyze the association between verticality tests and the most clinically affected body side. We calculated both the percentage of A-effect (expression of body tilt underestimation to the midline) and E-effect (expression of body tilt overestimation in the upright position). Individuals with PD showed greater variability in right SHV supination compared to the healthy control participants ( p = .002). There was greater clinical relevance in right (as opposed to left) SVV ( d = 0.83), right (as opposed to left) SHV pronation ( d = 0.91), and left (as opposed to right) SHV pronation ( d = 0.88). We observed a higher proportion of E-effect in individuals with PD. A significantly higher proportion of patients with PD, compared to patients in past literature, had right SHV pronation ( p = .001), left SHV pronation ( p = .023), right SHV supination ( p = .001), left SHV supination ( p = .046), and left SHV pronation ( p = .046). Thus, subjective visual and proprioceptive perception of verticality is altered in patients with PD, compared to individuals without PD.